2023
DOI: 10.1186/s10020-022-00599-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two laboratory model methods for diarrheal irritable bowel syndrome

Abstract: Background Diarrheal irritable bowel syndrome (IBS-D) is a common chronic functional gastrointestinal disorder, and the underlying pathogenic mechanism is still unclear. Animal models that mimic the pathological state of IBS-D patients were constructed to provide a reference for later drug research and model development. Methods The IBS-D model was induced using restraint stress and chemical stimulation (rhubarb), and rats were divided into normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The role of acetic acid produced by bacteria in the gut has recently been investigated in animal models [ 38 ]. It may also play a role in irritable bowel syndrome [ 39 ]. Acetic acid is present in very low concentrations in the cell, but greatly increased by bacteria in urinary tract infections [ 40 ], indicating that acetic acid is mainly derived from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The role of acetic acid produced by bacteria in the gut has recently been investigated in animal models [ 38 ]. It may also play a role in irritable bowel syndrome [ 39 ]. Acetic acid is present in very low concentrations in the cell, but greatly increased by bacteria in urinary tract infections [ 40 ], indicating that acetic acid is mainly derived from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Rat feces were collected individually 24 h after treatment completion, counted, and scored using Bristol fecal typing criteria 21 (Table 1). Feces were measured in wet weight (WW), then dried at a constant temperature of 60°C for 12 h and weighed as dry weight (DW).…”
Section: Methodsmentioning
confidence: 99%
“…Visceral sensitivity was evaluated using the abdominal withdrawal reflex (AWR) score using the colorectal dilatation method 21 . Rats were anesthetized with ether (LOT: 2204017, Xilong Scientific Co., Ltd, Shantou, China) after 12 h of fasting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that HS can alter the gut microbiota of animals such as mice, rabbits, and chickens. [10][11][12] Dysbiosis of the gut microbiota, characterized by decreased concentrations of beneficial metabolites such as short-chain fatty acids and increased levels of pathogenic metabolites, 13 can trigger excessive activation of the immune system, 14 resulting in intestinal inflammation and discomfort. 15 Secretory immunoglobulin A (sIgA), the primary immunoglobulin in the intestinal mucosa, is produced primarily by B cells and serves as the first line of defense against various endogenous microbial communities and exogenous invasive pathogens.…”
Section: Introductionmentioning
confidence: 99%